Size determination of Acipenser ruthenus spermatozoa in different types of electron microscopy - Psenicka, Martin; Tesarová, Martina; Tesitel, Jakub; Nebesárová, Jana (Micron (Oxford, England, 2010)
In this study three types of scanning electron microscopes were used for the size determination of spermatozoa of sterlet Acipenser ruthenus - high vacuum scanning electron microscope (SEM, JEOL 6300), environmental scanning electron microscope (ESEM, Quanta 200 FEG), field emission scanning electron microscope (FESEM, JEOL 7401F) with cryoattachment Alto 2500 (Gatan) and transmission electron microscope (TEM, JEOL 1010). The use of particular microscopes was tied with different specimen preparation techniques. The aim of this study was to evaluate to what degree the type of used electron microscope can influence the size of different parts of spermatozoa. For high vacuum SEM the specimen was prepared using two slightly different procedures. After chemical fixation with 2.5% glutaraldehyde in 0.1M phosphate buffer and post-fixation by 1% osmium tetroxide, the specimen was dehydrated by acetone series and dried either by critical point method or by means of t-butylalcohol. For ESEM fresh, unfixed material was used, which was dropped on microscopic copper grids. In FESEM working in cryo-mode the specimen was observed in a frozen state. Ultrathin sections from chemically fixed and Epon embedded specimens were prepared for TEM observation. Distinct parts of sterlet spermatozoa were measured in each microscope and the data obtained was statistically processed. Results confirmed that the classical chemical procedure of specimen preparation for SEM including critical point drying method led to a significant contraction of all measured values, which could deviate up to 30% in comparison with values measured on the fresh chemically untreated specimen in ESEM. Surprisingly sperm dimensions determinated on ultrathin sections by TEM are comparable with values obtained in ESEM or FESEM.
Keywords: Spermatozoa; Animals; Cell Size; mikroskopie elektronová rastrovací; Specimen Handling; mužské pohlaví; zvířata; odběr biologického vzorku; Fishes; Male; velikost buňky; spermie; Microscopy, Electron, Scanning; ryby